2019
DOI: 10.1136/bmjopen-2019-031452
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cardiovascular remodelling in fetuses and infants conceived by assisted reproductive technologies: a prospective observational cohort study protocol

Abstract: IntroductionAssisted reproductive technologies (ART), namely in vitro fertilisation and intracytoplasmic sperm injection, have become widely used to treat infertility. Although the use of ART is generally considered favourable, there are ongoing concerns about the prenatal and perinatal risks as well as long-term risks for the child. Epidemiological studies have demonstrated an association between pathological events during fetal development and future cardiovascular risk, raising concerns about cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The available data on long-term consequences is sparse, but neurodevelopmental deficits, abnormalities in glucose metabolism and the early development of metabolic syndrome are named as potential adverse health outcomes [ 11 , 15 , 37 ]. In the literature, cardiovascular remodeling within the ART offspring is assumed [ 16 , 18 , 39 ]. A well-known Swiss study reported generalized endothelial dysfunction, increased intima-media thickness and elevated arterial stiffness in a cohort of 65 ART singletons compared to 57 spontaneously conceived controls [ 17 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The available data on long-term consequences is sparse, but neurodevelopmental deficits, abnormalities in glucose metabolism and the early development of metabolic syndrome are named as potential adverse health outcomes [ 11 , 15 , 37 ]. In the literature, cardiovascular remodeling within the ART offspring is assumed [ 16 , 18 , 39 ]. A well-known Swiss study reported generalized endothelial dysfunction, increased intima-media thickness and elevated arterial stiffness in a cohort of 65 ART singletons compared to 57 spontaneously conceived controls [ 17 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was a prospective and observational cohort study; the detailed protocol was published previously [17]. Initially, we recruited 111 fetuses that had been conceived by ART and 106 controls at the gestational age of 28 +0 to 32 +6 weeks between December 2017 and April 2019 at the Department of Ultrasound, Shengjing Hospital of China Medical University, Shenyang, China.…”
Section: Studymentioning
confidence: 99%
“…Initially, we recruited 111 fetuses that had been conceived by ART and 106 controls at the gestational age of 28 +0 to 32 +6 weeks between December 2017 and April 2019 at the Department of Ultrasound, Shengjing Hospital of China Medical University, Shenyang, China. All participants were singletons, and without any structural or chromosomal anomalies, evidence of infection, or any maternal medical diseases [17]. Twenty-three ART fetuses and 21 controls were excluded due to prematurity, smoking during pregnancy, or small/large-for-gestational age (Fig.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations